Media Convergence in Technology and Content Aspects in the Digital Communication Era - Bayu Mukti (Formosa Journal of Applied Sciences, 2023)
This research is motivated by technological advances resulting in media convergence. This research aims to examine the existence of media convergence in technological and content aspects in the digital communication era. This media convergence is supported by technological developments so that media can be used digitally. This research was conducted using qualitative research methods and data collection using literature study. The results and discussion of this research are that technological developments and media convergence have an impact on people's lives. This innovation towards media convergence shows that there is an increase in the quality of human resources who are the subject of communicating and running communication media. It can be concluded that media convergence in this digital communication era, which is supported by internet technology, can help the development of communication media in today's society.